Virtual reference service as a tool of reference-information servicing of Tomsk State University Research Library - V. D. Schubert (Библиосфера)
Tomsk State University Research Library offers many information-library services. The virtual reference service is designed to carry on users' requests in a remote access mode. Its goal is to provide prompt assistance in obtaining information for users, consulting readers on their request, attracting information resources inaccessible to users during their query execution, and promoting the library resources and services. The article objective is to analyze the activity of the virtual reference service as a tool for users’ reference-information servicing in Tomsk State University Research Library for April 2013 - July 2017. Based on statistical indicators such as user status, number of requests, number of queries, inquiry types; user reviews) it concludes the importance of this activity direction and its development prospects.